Detection Of Students With Special Needs At 1 Kesik Public Elementary School - Devi Sri Wahyuni; Aswasulasikin Aswasulasikin; Abdul Aziz (Sumber Belajar Sejahtera, 2023)
This study aims to determine how to detect students with special needs early and can detect the presence of students with special needs in class 1 and grade 2. This research uses descriptive qualitative research methods, which are naturalistic research which aims to describe the early detection of students with special needs at SDN 1 Kesik. The results of this study are the procedures for implementing the identification of students with special needs carried out by teachers or homeroom teachers with several stages, namely: (a). collecting child data (b). transferring (c). calcifying student data (d). Holding intemal consultation meetings with all staff at the school: principal, homeroom teacher, special education teacher, subject teacher, and the entire team of teachers (e). organizing case meetings (f). preparing the final report. Identification procedures are carried out by teachers or homeroom teachers to find students who have barriers in the classroom. There are 3 students detected as having special barers at SDN 1 Kesik in the lower grades with 3 cognitive barrers, including (1) moderate speech difficulties, (1) severe cognitive difficulties, and one (1) student has more than 2 barriers, namely severe cognitive difficulties, moderate speech difficulties, and severe dyslexia